Methylammonium organic cation-substituted cesium bismuth bromide-based perovskite prepared via microwave-assisted solvothermal method for photovoltaic application - Low, Yiin Jian (2024)
Improving Cs-Bi-Br-based perovskites for optoelectronic applications necessitates fast synthesis and thorough investigation of A-site elements. This thesis focuses on the optimization of a microwave-assisted solvothermal method which offers a rapid synthesis for single (Cs3Bi2Br9) and double perovskite (Cs2AgBiBr6) materials. The microwave-assisted solvothermal method was optimized with solvent (isopropanol, hexane), ligand (oleic acid, oleylamine) and additive (hydrobromic acid) based on the Cs-Bi-Br-based perovskite materials. The structural and optical characteristics of the synthesized materials were investigated extensively for a better understanding on the material's properties. The research also explores the substitution effect of methylammonium organic cation (MA+) on the material’s properties of single perovskite (Cs3-xMAxBi2Br9) and double perovskite (Cs2-xMAxAgBiBr6). A phase segregation event happens in Cs3-xMAxBi2Br9 when x ≥ 1.0, causing the formation of Cs3Bi2Br9 and MA3Bi2Br9 structure with intermediate diffraction plane. Excess of MA+ substitution in Cs3-xMAxBi2Br9 reduces the ligands passivation effect and induced a polydisperse morphology. No significant changes were found in absorption bandgap, Urbach energy and exciton binding energy as MA+ substitution progress in Cs3-xMAxBi2Br9. The passivation in non-radiative recombination induced by the intermediate phase formation enhanced the emission intensity and carrier lifetime. Specific thermal decomposition pathway in Cs3-xMAxBi2Br9 was allocated when x = 0.5. While, insignificant amount of MA+ substitution (x = 0.2) relieves the microstrain in Cs2AgBiBr6 structure, increases the volume and reduces the crystallite size without triggering the silver bromide impurities formation. MA+ also induces defect in structure, causing an aggregation event happens in Cs2AgBiBr6. As the MA+ substitution increased in Cs2-xMAxAgBiBr6, the structural disorderment effect caused the absorption energy bandgap red-shifted, Urbach energy rose, and emission intensity reduced. Proper MA+ substitution (x = 0.6) in Cs2-xMAxAgBiBr6 enhanced the carrier lifetime, but came at the expense of generating a high density of non-radiative recombination. The thermal stability of the Cs2-xMAxAgBiBr6 is minimally impacted by MA+ substitution, as the allowed level of MA+ substitution is limited. Photovoltaic performance of pure Cs2AgBiBr6 surpasses the other materials with a power conversion efficiency of 0.019 %. This research contributes fundamental insights into the investigation of pristine and MA+-substituted Cs-Bi-Br based perovskite materials for future photovoltaic applications.